Limits of and Alternatives to Conventional Medicine in the Context of Terminal Illness (e.g., Palliative Care) - Bastianello, Stefania; Cattaneo, Daniela Antonella (ETHICS IN PROGRESS, 2022)
This paper aims at analysing the evolution of palliative care in the international context and their role in the path of care for the patient and the family. Method: born in 1967 by Cicely Saunder, palliative care were aimed at assisting the terminally ill, accommodating both the needs of the patient and the family. Not only to be cured or healed, but to be taken care of. The paper examines the definitions of palliative care provided by the World Helth Organization. We observe that palliative care is not only an effective and timely response to the clinical, psychological, social and spiritual needs of the sick person and their family in an advanced and terminal stage, but an integrated care to support specialist treatment in the presence of an advanced disease picture; a space for in-depth study for the sick person and the family so that the sick person can consciously and freely choose the available treatment proposals, their limits and their consequences. A treatment path in which the transparency of the proposals is a condition for building a shared consensus with the patient and adequate communication with the family. Palliative care has acquired its own identity, its own role in the path of care for the patient and the family, pursuing the proportionality of therapeutic options and the support of the patient and the family without discrimination, with equity and equality.